PENGARUH PERFORMA VIDEO TERHADAP JUMLAH VIEWS VIDEO REGULER DI YOUTUBE MENGGUNAKAN ANALISIS JALUR - Muhammad Adam Ashar; Fuad Muhajirin Farid; Selvi Annisa (Universitas Lambung Mangkurat, 2023)
YouTube is a video-sharing website which is one of the media for deployment information that is of great interest to the public in Indonesia. Being the most visited website in the world, YouTube has had a significant impact on modern society. Many people in Indonesia have utilized YouTube as a platform to share their thoughts and creativity through the video they create, as well as to make income. Creative content will usually get more responses from the audience. Creating a regression model for use in path analysis enables the investigation of causal links between various variables. The intention of this study is to specify the path's structure and analyze what variables effect YouTube video views. The exogenous variables used to observe the influence of views are impressions, CTR and watch time. This study uses path analysis to examine how video performance impacts views both directly and indirectly using path diagrams. Considering the outcomes of this study, the variables that affect views are impressions and CTR. Impressions have an indirect effect on Watch Time and Views but smaller than the direct effect, so the best path to increase views is the direct effect path of impressions. Impressions have a direct effect of 1,214 while CTR has a direct effect on views of 1,077. Keywords: YouTube, Views, Path Analysis, Direct Effect